Penyediaan Infrastruktur Pengelolaan Air Limbah Domestik di Kawasan Wisata Danau Toba - Benny Kusdinar (Yayasan Literasi Sains Indonesia, 2026)
Lake Toba is one of the main tourist destinations in Indonesia. Still, it now faces serious problems, including declining air quality due to pollution, particularly from household wastewater and floating net cage (KJA) fisheries. This research employs a descriptive qualitative approach, supported by quantitative data. The results show that the initiation of the Parapat-Ajibata off-site wastewater management project began in 1994/1995 and was realized with the construction of a DWWTP in 1997 in Sijambur Village, Ajibata District, Toba Regency, with a capacity of 2,010 m3 per day and a piping network to serve the Parapat-Ajibata City area. Unfortunately, this utilization accounts for only 10% of the installed capacity, which is attributed to low community involvement, inadequate supervision and infrastructure, and institutional issues. As a follow-up to minimize domestic wastewater in the Parapat Tourism City, the Free Beach Domestic Wastewater Treatment Plant with a capacity of 518 m3 per day has been built in 2021 and the Ajibata Faecal Sludge Treatment Plant with a capacity of 10 m3 per day in 2024 which is integrated with the Ajibata DWWTP, which is a necessity to address on-site service issues so as to prevent environmental impacts, improve public health and sustainable social and economic growth in the Lake Toba tourism area.